EURO-NMD registry: federated FAIR infrastructure, innovative technologies and concepts of a patient-centred registry for rare neuromuscular disorders - Atalaia, Antonio; Wandrei, Dagmar; Lalout, Nawel; Thompson, Rachel; Tassoni, Adrian; 't Hoen, Peter A C; Athanasiou, Dimitrios; Baker, Suzie-Ann; Sakellariou, Paraskevi; Paliouras, Georgios; D'Angelo, Carla; Horvath, Rita; et al. (Orphanet journal of rare diseases, 2024)
BACKGROUND: The EURO-NMD Registry collects data from all neuromuscular patients seen at EURO-NMD's expert centres. In-kind contributions from three patient organisations have ensured that the registry is patient-centred, meaningful, and impactful. The consenting process covers other uses, such as research, cohort finding and trial readiness. RESULTS: The registry has three-layered datasets, with European Commission-mandated data elements (EU-CDEs), a set of cross-neuromuscular data elements (NMD-CDEs) and a dataset of disease-specific data elements that function modularly (DS-DEs). The registry captures clinical, neuromuscular imaging, neuromuscular histopathology, biological and genetic data and patient-reported outcomes in a computer-interpretable format using selected ontologies and classifications. The EURO-NMD registry is connected to the EURO-NMD Registry Hub through an interoperability layer. The Hub provides an entry point to other neuromuscular registries that follow the FAIR data stewardship principles and enable GDPR-compliant information exchange. Four national or disease-specific patient registries are interoperable with the EURO-NMD Registry, allowing for federated analysis across these different resources. CONCLUSIONS: Collectively, the Registry Hub brings together data that are currently siloed and fragmented to improve healthcare and advance research for neuromuscular diseases.
Keywords: Registry Hub; Registries; Registry; Humans; neuromuskulární nemoci; lidé; Neuromuscular Diseases; vzácné nemoci; Rare Diseases; registrace; FAIR data